Penggunaan dan Fungsi Musik Talempong Unggan pada Acara Baralek di Nagari Unggan Kecamatan Sumpur Kudus Kabupaten Sijunjung - Deby Indrawati; Marzam Marzam (SENDRATASIK UNP, 2022)
This study aims to describe the use and analysis of the function of Talempong Uggan Music at the Baralek Event in Nagari Uggan, Sumpur Kudus District, Sijunjung Regency. This type of research is a qualitative research using descriptive analysis method. The main instrument in this research is the researcher himself and is assisted by supporting instruments such as stationery and camera. Data collection techniques were carried out by means of library research, observation, interviews and documentation. Data analysis was carried out by collecting data, describing data, and concluding data. The results showed that the use of Talempong Uggan Music in a series of Baralek Events in Nagari Uggan was at the bararak from Bako's house to the main house, where the bride and groom and their entourage were paraded using Talempong to the bride's residence. Furthermore, at the Basalawat event at night, the aim is to escort the groom along with Niniak mamak and his entourage using Talempong to the bride's house. At the Manyombah Mintuo event, the bride is paraded to the groom's house, then Baarak Iriang is performed from the bride's house from the groom's house to the accompaniment of Talempong unggan as an accompaniment for the entire series of baralek events. The function of Talempong Unggan music in Nagari Unggan is as a function of expression, a function of aesthetic enjoyment, an entertainment function, a communication function, and an economic resource function for musicians.